2021
DOI: 10.1038/s41598-021-92871-z
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent YAP/TAZ and SMAD signaling mediate vocal fold fibrosis

Abstract: Vocal fold (VF) fibrosis is a major cause of intractable voice-related disability and reduced quality of life. Excision of fibrotic regions is suboptimal and associated with scar recurrence and/or further iatrogenic damage. Non-surgical interventions are limited, putatively related to limited insight regarding biochemical events underlying fibrosis, and downstream, the lack of therapeutic targets. YAP/TAZ integrates diverse cell signaling events and interacts with signaling pathways related to fibrosis, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 61 publications
1
27
0
Order By: Relevance
“…An immortalized human VF fibroblast cell line, HVOX, 29 and macrophages derived from THP‐1 (ATCC, Manassas, Virginia, U.S.A.) were treated with 10 ng/ml TNF‐α, 100 ng/ml IFN‐γ, or 40 ng/ml IL4 ± various concentrations of GCs for 24 h.…”
Section: Methodsmentioning
confidence: 99%
“…An immortalized human VF fibroblast cell line, HVOX, 29 and macrophages derived from THP‐1 (ATCC, Manassas, Virginia, U.S.A.) were treated with 10 ng/ml TNF‐α, 100 ng/ml IFN‐γ, or 40 ng/ml IL4 ± various concentrations of GCs for 24 h.…”
Section: Methodsmentioning
confidence: 99%
“…As expected, the inhibition of the YAP signaling pathway by siRNA against YAP reversed the inhibitory effect of S1PR2 overexpression on the phosphorylation of YAP at Ser127 (Figure 6B). Previous investigations showed that the YAP nuclear localization was involved in the regulation of the canonical profibrotic signaling pathway TGF‐β 30 . We next investigated whether S1PR2 influenced TGF‐β signaling via the YAP pathway in HLSECs.…”
Section: Resultsmentioning
confidence: 99%
“…38 In consistence with previous studies, we detected that YAP dephosphorylation and nuclear localization were induced by S1pr2 signaling in liver sinusoidal endothelial cells. Furthermore, it has been shown that the YAP/TGF-β signaling was involved in the regulation of fibroblast proliferation migration and myofibroblasts differentiation, and therefore tightly controlled tissue fibrosis after injury, 30,39,40 suggesting that LSEC-S1pr2-YAP signaling might be involved in the modulation of HSC functions that determined the development of tissue fibrosis. Nakamura R et al reported that YAP/TAZ integrated diverse cell signaling events and interacted with signaling pathways related to tissue fibrosis, including the TGF-β/SMAD pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides miRNAs, protein components in the pMSC-exos are also considered to play a key role in inhibiting the YAP signaling pathway, which needs to be investigated in the future. Moreover, it has been reported that TGFβ1 also activate YAP in fibroblasts (Nakamura et al, 2021); thus, the inhibitory effect of pMSC-exos on the YAP signaling pathway may also be related to their targeted regulation of TGFβ1.…”
Section: Pmsc-exos Prevent En1 Activationmentioning
confidence: 98%